The interaction between seminal plasma, sperm, and endometrium in inter- and intra-species breeding in equids - Podico, Giorgia; Bittar, João H.; Loux, Shavahn C.; Souza, Fabiana F. [UNESP]; Canisso, Igor F. (Oxford University Press (OUP), 2024)
Anecdotal experience suggests horse mares have less post-breeding inflammation and better fertility when bred with donkeys. This study aimed to compare the post-breeding inflammatory response of mares exposed to donkey and horse semen and seminal plasma and evaluate the proteome and metabolome of donkey and horse sperm and seminal plasma. Uterine edema, intrauterine fluid accumulation, polymorphonuclear neutrophils on cytology, and concentrations of progesterone, and pro- and anti-inflammatory cytokines (IL1A, IL1B, IL4, IL6, CXCL8, IL10) were assessed pre- and post infusion of semen and seminal plasma (donkey and horse). The metabolome and proteome were analyzed by LC-MS/MS. Mare cycles bred with horse semen had a greater progesterone concentration than those bred with donkey semen at 8 days post ovulation (P = 0.046). At 6 h post infusion, the inflammatory response due to the donkey semen tended to be lower (P = 0.074). Donkey seminal plasma had anti-inflammatory properties compared to horse semen and seminal plasma, as determined by fewer neutrophils on uterine cytology (P < 0.05). Horse semen resulted in greater concentrations of IL6 and lesser concentrations of IL1B (P < 0.05). PGE1, PGE3, and lactoferrin concentrations were significantly more abundant in donkey sperm and seminal plasma. Prostaglandins play an important role in immunomodulation and might contribute to the response triggered in interspecies breeding. In conclusion, breeding horse mares with donkey semen induces similar post-breeding endometritis as observed with horse semen. Donkey seminal plasma results in a lower post-infusion inflammatory response compared to other combinations in the immediate post-breeding.